2006
DOI: 10.1159/000092986
|View full text |Cite
|
Sign up to set email alerts
|

Changing Spectrum of Squamous Cell Abnormalities Observed on Papanicolaou Smears in Mubarak Al-Kabeer Hospital, Kuwait, over a 13-Year Period

Abstract: Objective: The aim of this study was to determine the incidence of squamous cell abnormalities in cervical cytology in Mubarak Al-Kabeer Hospital, Kuwait, and to document any change in the pattern of these lesions. Materials and Methods: Over a 13-year period (1992–2004), 86,434 cervical smears were studied in Mubarak Al-Kabeer Hospital, Kuwait. Conventional Pap smears were first examined by cytotechnicians and finally reported by cytopathologists. The smears were classified according to the modified Bethesda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
4
25
1
Order By: Relevance
“…Similar studies have shown the percentage of inadequate smears have ranged from 0.2% to 13.94%. [14][15][16] The proportion of satisfactory samples received was impressively high as in our institute cervical smears were taken by trained gynecologists and then send to department of pathology for analysis, therefore, reducing costs and inconvenience of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have shown the percentage of inadequate smears have ranged from 0.2% to 13.94%. [14][15][16] The proportion of satisfactory samples received was impressively high as in our institute cervical smears were taken by trained gynecologists and then send to department of pathology for analysis, therefore, reducing costs and inconvenience of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Urmila Banik et al [3] in Bangla Desh in 2010 they found ,ASCUS -0.18 %, AGC-0.12%, L SIL-6.36 % ,H SIL-1.18 % , and malignancy -0.35 %. According to another study in Brazil [10] on 18,22,441 pap smears in 5 years, L SIL was found in the age group of 15-30 years, high grade lesions including cancer cervix were found in women aged 40 years and above. According to our study ASCUS was found in 0.19%, L SIL was found in 0.96 % in the age group of 35-39.…”
Section: Discussionmentioning
confidence: 93%
“…Cytological diagnosis in relation to age. Arabia, and 6.8% in New Delhi India respectively [16] [17] [18]. The worldwide range of positive cytology from the conventional Pap smear is 10% [19].…”
Section: Discussionmentioning
confidence: 99%